2003
DOI: 10.1042/bj20030420
|View full text |Cite
|
Sign up to set email alerts
|

Induced expression of manganese superoxide dismutase by non-toxic concentrations of oxidized low-density lipoprotein (oxLDL) protects against oxLDL-mediated cytotoxicity

Abstract: Oxidized low-density lipoprotein (oxLDL) affects macrophages and plays a critical role in the development of atherosclerosis. In the present paper, we demonstrate that high concentrations of oxLDL provoked apoptosis of human Mono-Mac-6 cells, which was blocked by diphenylene-iodonium (DPI), an inhibitor of flavin-containing enzymes, such as NADPH oxidase, suggesting the involvement of reactive oxygen species (ROS). Importantly, pre-treatment of cells with low concentrations of oxLDL prevented apoptosis in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 47 publications
2
12
0
1
Order By: Relevance
“…Many investigations indicated that MnSOD may play roles to protect against atherosclerosis and plaque formation. MnSOD is reported to inhibit the oxidation of low density lipid and protect against endothelial dysfunction [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations indicated that MnSOD may play roles to protect against atherosclerosis and plaque formation. MnSOD is reported to inhibit the oxidation of low density lipid and protect against endothelial dysfunction [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, oxLDL can also contribute to the adaptive antiatherogenic responses of endothelium through the transcriptional regulation of antioxidant enzymes (2,23,36). Mitochondrial involvement is implied from the finding that nontoxic concentrations of oxLDL lead to induction of manganese superoxide dismutase and complex I (9,50). Many of these responses can be recapitulated using defined lipid oxidation products such as the electrophilic cyclopentenones (25,33).…”
mentioning
confidence: 88%
“…50 SOD2 is inactivated by ONOO − 51 and its activity is decreased with age 52 . Expression of SOD2 is upregulated by various cytokines and agonists in a redox-dependent manner 53 . SOD2 overexpression attenuates H 2 O 2 -induced apoptosis, 54 decreases lipid peroxidation and reduces the age-related decline in mitochondrial ATP.…”
Section: Mitochondrial Function and Production Of Mitochondrial Rosmentioning
confidence: 99%